Failed Educational Reform in the New York City School System - Dupre, Andrea (Radical Teacher, 2018)
Like the horrifying photographs journalists take of the innocent victims of senseless-seeming wars, the article’s lens zeroes in on the destruction of a once highly regarded Manhattan high school whose story needs to be told. The article sheds light on what the NYC Department of Education would like to keep buried, the revelation of a shameful mismanagment of a school community by among other things, a misguided pair of principals assigned during the administration of Mayor Michael Bloomberg. The school - unlike those with more economically priveleged student bodies - was rendered powerless by virtue of its demographics and lack of cultural capital.